Body and Wing Allometries Reveal Flight-Fecundity Tradeoff in Response to Larval Provisioning in Osmia lignaria (Hymenoptera: Megachilidae). Issue 3 (11th June 2021) - Helm, Bryan R; Baldwin, Maxwell A; Rinehart, Joseph P; Yocum, George D; Greenlee, Kendra J; Bowsher, Julia H
Abstract: Variation in body size has important implications for physical performance and fitness. For insects, adult size and morphology are determined by larval growth and metamorphosis. Female blue orchard bees, Osmia lignaria, (Say) provision a finite quantity of food to their offspring. In this study, we asked how provision-dependent variation in size changes adult morphology. We performed a diet manipulation in which some larvae were starved in the final instar and some were given unlimited food. We examined the consequences on adult morphology in two ways. First, allometric relationships between major body regions (head, thorax, abdomen) and total body mass were measured to determine relative growth of these structures. Second, morphometrics that are critical for flight (wing area, wing loading, and extra flight power index) were quantified. Head and thorax mass had hyperallometric relationships with body size, indicating these parts become disproportionately large in adults when larvae are given copious provisions. However, abdominal mass and wing area increased hypoallometrically with body size. Thus, large adults had disproportionately lighter abdomens and smaller wing areas than smaller adults. Though both males and females followed these general patterns, allometric patterns were affected by sex. For flight metrics, small adults had reduced wing loading and an increased extra flight power index. These results suggest that diet quantity alters development in ways that affect the morphometric trait relationships in adult O. lignaria and may lead to functional differences in performance.